2016
DOI: 10.3389/fpls.2016.01814
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Increases the Chilling Tolerance of Chloroplast in Cucumber Seedlings by Regulating Photosynthetic Electron Flux and the Ascorbate-Glutathione Cycle

Abstract: The aim of the study was to monitor the effects of exogenous melatonin on cucumber (Cucumis sativus L.) chloroplasts and explore the mechanisms through which it mitigates chilling stress. Under chilling stress, chloroplast structure was seriously damaged as a result of over-accumulation of reactive oxygen species (ROS), as evidenced by the high levels of superoxide anion (O2−) and hydrogen peroxide (H2O2). However, pretreatment with 200 μM melatonin effectively mitigated this by suppressing the levels of ROS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 70 publications
12
58
0
Order By: Relevance
“…Accumulating studies on the protective mechanisms of melatonin against stress conditions showed a complex correlation to ROS production. Several studies have demonstrated that melatonin is capable to regulate the elements involved in the redox network . For example, melatonin treatment significantly decreased the amount of ROS content in plants exposed to salinity and drought stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies on the protective mechanisms of melatonin against stress conditions showed a complex correlation to ROS production. Several studies have demonstrated that melatonin is capable to regulate the elements involved in the redox network . For example, melatonin treatment significantly decreased the amount of ROS content in plants exposed to salinity and drought stress .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports that melatonin could scavenge ROS and defense against oxidative damage in plants . Gene expression of redox homeostasis‐related enzymes such as peroxidases and glutathione peroxidase was up‐regulated under various stresses in plants .…”
Section: Introductionmentioning
confidence: 99%
“…Two molecules of GSH are utilized by DHAR to reduce DHA to AsA, and during this reaction, GSSG is generated (Gill and Tuteja 2010). Previous studies have shown that exogenous PGRs increased the content of AsA and GSH under low temperature stress, reduced the oxidative damage in plant cells, and improved the tolerance to stress (Liu et al 2009, 2011, Balestrasse et al 2010, Manafi et al 2015, Nahar et al 2015, Zhao et al 2016. Our results revealed that chilling stress led to the increase in AsA, DHA, and total AsA contents in both soybean varieties ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chilling stress is one of the destructive abiotic stresses that restricts photosynthesis and eventually limits agricultural production and quality of tropical and subtropical plants (Allen and Ort 2001, Ikeda et al 2009, Liu et al 2012, Nahar et al 2015. Reduction in electron transport (Zhao et al 2016) and photosynthetic efficiency, and changes in protein structure and enzyme activities are some of the most common and primary chilling injury symptoms within plants. Inhibition of the carbon reduction cycle (Allen and Ort 2001), PSII activity (Strauss et al 2006), and photosynthesis (Savitch et al 1997, Allen andOrt 2001) under chilling stress increases generation of reactive oxygen species (ROS) (Gill andTuteja 2010, Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation